Respostas
respondido por:
1
Boa noite
f(x) = 2x -3 : f(x) = 11
11 = 2x -3
2x = 11 +3
x = 14/2
x = 7
Bons estudos!!
f(x) = 2x -3 : f(x) = 11
11 = 2x -3
2x = 11 +3
x = 14/2
x = 7
Bons estudos!!
respondido por:
1
Resolução:
f(x) = 2x - 3
f(x) = 11
portanto temos que;
2x - 3 = 11
2x = 11 + 3
x = 14 / 2
x = 7
bons estudos:
f(x) = 2x - 3
f(x) = 11
portanto temos que;
2x - 3 = 11
2x = 11 + 3
x = 14 / 2
x = 7
bons estudos:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás